Evaluating the satisfaction of FROG VLE in primary school using learners' value index satisfaction (LEVIS) framework: a case study at Sekolah Kebangsaan Taman Nirwana (SKTN) / Lizawati Abdul Wahab - Abdul Wahab, Lizawati (2015)
This study assessed the extent of user satisfaction FROG VLE in Sekolah Kebangsaan Taman Nirwana (SKTN) by making year five and year six students as participants of this study. By using of quantitative method, questionnaire has been used in this research by using Learners' Value Index Satisfaction (LeVIS) Framework as a model to assess the satisfaction. This research found that average level of user satisfaction among year five and year six in SKTN who use the Frog VLE are in satisfied level. However, the numbers of the Frog VLE users in SKTN are still at a low level, which is about 35% only of the total of year five and year six student. Five extracted factors produced after did the rotations which are technology self-efficacy factor, learning enjoyable factor, interaction factor, commitment factor, and family influence factor. From the analysis also, two items from the questionnaire have been removed, which are access from everywhere via internet, and interesting subject matter. Two recommendations are given to increase the number of users Frog VLE onwards, the level of user satisfaction at SKTN, which are to increase computer and Internet facilities for users, to give the best and familiar identification (ID) to the user especially for primary students. Limitation of this research is only focus on the year five and year six students in Sekolah Kebangsaan Taman Nirwana (SKTN) in order to evaluate the user satisfaction of Frog VLE program. So the accuracy of the sampling due to fact that demographic profile also will gives an impact to the survey. Research within greater scope for further research is needed to obtain more accurate results.